Susceptibility toward cefiderocol and sulbactam-durlobactam in extensively drug-resistant Acinetobacter baumannii detected from ICU admission screening in Hanoi, Vietnam, 2023 - Sébastien Boutin; Nguyen Quang Toan; Thi Anh Mai Pham; Truong Nhat My; Nguyen Thi Kim Phuong; Bui Tien Sy; Nguyen Van Trong; Lisa Göpel; Leo Huber; Kaan Kocer; Le Thi Kieu Linh; Tran Thanh Tung; et al. (Microbiology Spectrum)
ABSTRACT Infections due to carbapenem-resistant Acinetobacter baumannii (CRAB) pose significant clinical challenges due to limited treatment options. In this study, we investigated the molecular epidemiology, resistance profiles, and genomic characteristics of CRAB isolates from intensive care unit (ICU) admission screenings in Vietnam, focusing on susceptibility to the novel agents cefiderocol and sulbactam-durlobactam. Between 1 July and 31 October 2023, extended antibiotic susceptibility testing (AST) and whole-genome sequencing were performed on CRAB isolates obtained through ICU admission and weekly screenings at the 108 Military Central Hospital in Hanoi. CRAB colonization was detected in 31 of 691 ICU patients (4.5%), with 30 isolates classified as multidrug-resistant/extensively drug-resistant and an STpas164 isolate resistant to all substances tested except for sulbactam-durlobactam. All isolates were resistant to ciprofloxacin, levofloxacin, imipenem, and meropenem, with high resistance rates to amikacin (96.8%) and trimethoprim/sulfamethoxazole (96.8%). Cefiderocol resistance was found in four STpas164 isolates and one STpas338-1LV (16.1%), displaying alterations in pirA and piuA genes, while sulbactam-durlobactam non-susceptibility (61.3%) was observed in isolates carrying PBP3 alterations. Molecular characterization revealed high-risk clades, with STpas2 as the most prevalent, followed by the emerging STpas164 and STpas16 clones, which showed significant resistance and virulence potential. CRAB prevalence among ICU patients and the emergence of highly resistant clones show the need for surveillance and alternative therapeutic options. The presence of cefiderocol resistance and the high rate of sulbactam-durlobactam non-susceptibility in CRAB isolates without prior exposure raise concerns about the spread of resistance in asymptomatic carriers. AST should be performed before using novel antibiotic agents.IMPORTANCECarbapenem-resistant Acinetobacter baumannii (CRAB) is a highly drug-resistant bacterium that poses a serious threat in hospitals, especially to patients in intensive care units (ICUs). This study examined CRAB bacteria found in ICU patients in Vietnam, focusing on their resistance to antibiotics, including new antibiotics such as cefiderocol and sulbactam-durlobactam. The results showed that CRAB in Vietnam is resistant to almost all the antibiotics tested, making infections extremely difficult to treat. Alarmingly, some bacteria were resistant to cefiderocol and sulbactam-durlobactam even in patients who had never received these drugs, suggesting that resistance is spreading quietly. This highlights the urgent need for ongoing surveillance, early detection, and careful use of antibiotics to prevent the spread of untreatable infections.